(untitled) (Journal of responsible AI & ethics, 2026)
Artificial intelligence (AI) is increasingly being used in predictive policing and surveillance systems, with the aim of improving law enforcement efficiency and crime prevention. However, the use of AI in these contexts has raised significant ethical concerns related to bias, privacy, transparency, and accountability. Predictive policing algorithms, which forecast criminal activity based on historical data, have been criticized for perpetuating existing biases and disproportionately targeting marginalized communities. Additionally, surveillance systems powered by AI, such as facial recognition technology, have sparked debates over civil liberties and individual freedoms. This paper examines the ethical implications of AI in predictive policing and surveillance, focusing on how these technologies impact society, particularly with regard to discrimination, social justice, and human rights. Through a combination of theoretical analysis, case studies, and empirical research, the paper explores the challenges of ensuring fairness and equity in AI systems, and offers recommendations for mitigating ethical risks.